La enseñanza del español a través de un cuento africano - Jacqueline Boufack Tsamo Makouaka (Recherches)
Artistic and cultural heritage is composed of countless elements that contribute to the construction of each individual’s identity, such as language, art, tales, and more. A tale, to paraphrase Léopold Sédar Senghor, is the pictorial expression of a moral truth, both knowledge of the world and a lesson in social life. In other words, the tale has several functions, such as ludic, initiatory, didactic and pedagogic. It is a pedagogical element in itself, because it involves society and embodies its values. In this paper we evaluate its didactic potential by using an African tale.